PERFORMANCE-BASED STRUCTURAL ANALYSIS ON STEEL FRAME MODULAR BUILDING SYSTEMS IN JAKARTA - Ilham Widiyantoko, Muhammad
Superiority in productivity, quality, and sustainability of modular-based buildings can serve as an alternative to balance infrastructure equity effort in Indonesia. However, limited knowledge and specific design references, along with the challenges of stability of modularbased structures – are the main challenges in implementing this technology conventionally. This study is proposed to find the response modification factor as means to develop design guide for modular-based building. The introduction of both, internal stabilization system (internal module wall) and hybridization of an external stabilization system (in-situ steel braced frame), serve as strategies that can be implemented to enhance structural strength and stability, as well as improvement to its failure mode. Response Spectrum Analysis, Non-Linear Pushover Analysis, and Time History Analysis respectively conducted to analyze 3 main structural performance parameters, namely; strength (element capacity-requirement ratio), stiffness (stability and global responsiveness of the building), and typical failure pattern (plastic hinge formation hierarchy). Furthermore, fragility study initiated with incremental dynamic analysis complement the investigation of seismic vulnerability of modular buildings. The results of this fragility analysis will be correlated with the typical structural fragility from HAZUS and risk-targeted design requirements in accordance with SNI 1726:2019. The findings reported in this study are expected to explain the global seismic performance of modular buildings.